2020
DOI: 10.1007/s11912-020-00962-3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions that Facilitate Shared Decision-Making in Cancers with Active Surveillance as Treatment Option: a Systematic Review of Literature

Abstract: Purpose of review Medical decisions concerning active surveillance are complex, especially when evidence on superiority of one of the treatments is lacking. Decision aids have been developed to facilitate shared decision-making on whether to pursue an active surveillance strategy. However, it is unclear how these decision aids are designed and which outcomes are considered relevant. The purpose of this study is to systematically review all decision aids in the field of oncological active surveillance strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Furthermore, DAs favorably affect clinical outcomes by enhancing risk perception accuracy (Stacey, Légaré, Lewis, Barry, et al, 2017; van Weert et al, 2016) and adherence (Nathan et al, 2016; Paskins et al, 2020; Song et al, 2022; Torres Roldan et al, 2021). The findings of some studies indicated that the implementation of DA interventions resulted in significant improvements in patient satisfaction (Berlin et al, 2019; Collée et al, 2020; Grüne et al, 2021; Staszewska et al, 2017; Tong et al, 2021; Wieringa et al, 2019; Yang et al, 2022), health (Grüne et al, 2021; Staszewska et al, 2017), and emotional (Staszewska et al, 2017; Violette et al, 2015; Vromans, Tenfelde, et al, 2019) outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, DAs favorably affect clinical outcomes by enhancing risk perception accuracy (Stacey, Légaré, Lewis, Barry, et al, 2017; van Weert et al, 2016) and adherence (Nathan et al, 2016; Paskins et al, 2020; Song et al, 2022; Torres Roldan et al, 2021). The findings of some studies indicated that the implementation of DA interventions resulted in significant improvements in patient satisfaction (Berlin et al, 2019; Collée et al, 2020; Grüne et al, 2021; Staszewska et al, 2017; Tong et al, 2021; Wieringa et al, 2019; Yang et al, 2022), health (Grüne et al, 2021; Staszewska et al, 2017), and emotional (Staszewska et al, 2017; Violette et al, 2015; Vromans, Tenfelde, et al, 2019) outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Some SRs found that DAs improve healthcare decision‐making and reduce anxiety and depression in patients (Collée et al, 2020; Spronk et al, 2019; Violette et al, 2015; Vromans, Tenfelde, et al, 2019) This suggests that DAs help improve the overall well‐being of patients, in addition to enhancing their ability to make effective decisions. The findings of these investigations need to be confirmed by additional research and a study on the potential mechanisms by which DAs may positively impact mental health outcomes should be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should not merely be selected to avoid treatment-related complications. Thus, it is recommended that shared decision-making techniques and decision aids be used to support careful deliberation about AS [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…thyroglobulin). In view of this situation, participatory decision making between physicians and informed patients, which is in principle required today anyway, is of particular importance (5,37). In the absence of strong evidence, the patient must be sufficiently informed about the evidence available and its background.…”
Section: Importance Of the Situation For Decision Makingmentioning
confidence: 99%